Big dumb eyes eaudiobook Stories from a simpler mind. - Bargatze, Nate (2025)
From one of the hottest stand-up comedians, Nate Bargatze brings his everyman comedy to the page in this hilarious collection of personal stories, opinions, and confessions. Nate Bargatze used to be a genius. That is, until the summer after seventh grade when he slipped, fell off a cliff, hit his head on a rock, and "my brain got, like, dented or something." Before this accident, he dreamed of being "an electric engineer, or a brain doctor, or maybe a math person who does like, math things for a living." Afterwards, a voice in his head told him, "It's okay. You're dumb now. All you got is standup."* But Nate went on to become one of today's top-grossing , record-breaking comedians. In Big Dumb Eyes, Nate talks about life as a non-genius. From stories about his first car (named Old Blue, a clunky Mazda with a tennis ball for a stick shift), life as a Southerner, and his first apartment where a rat chewed a hole right through the wall, to how his wife keeps him in line—and so much more. He also reflects on Vandy football and the origins of sushi (how can a Philadelphia roll be from old-time Japan!?). Nate's book is full of heart and will make readers laugh out loud—but it probably won't make them think too much. *Nate's family disputes this entire story.